Vilken är den teoretiskt optimala toppdiametern på bokmassaved vid motormanuell avverkning? - Olsson, Roger (2014)
The bioenergy market has been introduced relatively late in a perspective of the Swedish forestry. Nowadays branches and tops are used more frequently as bioenergy after harvesting. Therefore, it has developed a competitive situation between pulpwood and bioenergy. This situation has even established some questions. Two examples of these are: • At what top diameter should the final piece of pulpwood be crosscut to get the best economically result? • Should the top diameter, at the final piece of pulpwood, be crosscut at a thicker or smaller diameter than what is done today? The purpose of this report is to answer these two questions when the harvesting is made motor manually in beech stands. The principal of this report, Stora Enso Bioenergi AB, even wants to have a product tool for use in the determining of the theoretically optimal top diameter at a given time as the price of pulpwood, bioenergy and even the cost of harvesting is fluctuating. Therefore has even a practical calculation tool in Microsoft Excel been developed in this thesis. To facilitate future calculation when it comes to stands harvested by harvesters the calculation tool even includes the factors necessary for this. To obtain the essential input factors a field study was preformed. Diameters including bark, bark thickness, length and processing time of the last piece of pulpwood were collected. Thirty pieces of pulpwood were examined. After the field study volumes, harvesting costs and net value were calculated. During the field study the motor manual feller even emphasized that the chipping method is very important to decide where to make the crosscutting. The logger informed that the last piece of pulpwood was crosscut at a bigger top diameter when the chipping was made inside the stand compared to if a forwarder transported the branches and the tops out from the stand and the chipping occurred afterwards. By using quadratic regressions for the net value of pulpwood and bioenergy the theoretically optimal top diameter for each individual piece of pulpwood could be calculated. Then the average of these top diameters was estimated. This average turned out to be 6,3 centimetres including bark. The study even shows that the actual average of the top diameter in practically manual harvesting was 16,3 centimetres including bark. This indicates that the top diameter should be crosscut at a smaller diameter than what is done today.